2023
DOI: 10.1039/d3tc02707d
|View full text |Cite
|
Sign up to set email alerts
|

Light blue rigid excited-state intramolecular proton transfer organic semiconductor laser chromophores

Ilene Allison,
Mashashi Mamada,
Atul Shukla
et al.

Abstract: The effect of excited-state intramolecular proton-transfer (ESIPT) laser material rigidity on photophysical properties and amplified spontaneous emission (ASE) thresholds (EASEth) is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Excited-state proton transfer (ESPT) 1 is a fundamental process in chemistry and biology that has gained significant attention due to its diverse applications, 2 including in white light-emitting diodes (LEDs), 3 light-driven proton pumps by bacteriorhodopsin, 4 and fluorescent protein-based biosensors for cation detection. 5 From a molecular structure perspective, the ESPT process can be classified into intramolecular and intermolecular proton transfer processes (ESIntraPT and ESInterPT, Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Excited-state proton transfer (ESPT) 1 is a fundamental process in chemistry and biology that has gained significant attention due to its diverse applications, 2 including in white light-emitting diodes (LEDs), 3 light-driven proton pumps by bacteriorhodopsin, 4 and fluorescent protein-based biosensors for cation detection. 5 From a molecular structure perspective, the ESPT process can be classified into intramolecular and intermolecular proton transfer processes (ESIntraPT and ESInterPT, Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research in excited-state intramolecular proton transfer (ESIPT) has revealed its essential role in various applications such as luminescent materials, [1] organic light-emitting diodes, [2,3] bioimaging probes, [4,5] photoswitches, [6,7] and molecular logic gates. [8,9] ESIPT molecules typically exist in two tautomeric forms: enol (E) and keto (K).…”
Section: Introductionmentioning
confidence: 99%